2012
DOI: 10.1016/j.ijid.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor necrosis factor gene single nucleotide polymorphisms in the natural course of 2009 influenza A H1N1 virus infection

Abstract: The -238 A SNP allele of the TNF gene imposes on the course of 2009 H1N1 virus infection and is an independent risk factor for pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 23 publications
1
34
0
1
Order By: Relevance
“…The analysis of the selected SNPs was done using the restriction fragment length polymorphism method. The applied primers and reaction conditions are presented in table 1 [16,17]. Haplotype calculations were done using Unphased [18].…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of the selected SNPs was done using the restriction fragment length polymorphism method. The applied primers and reaction conditions are presented in table 1 [16,17]. Haplotype calculations were done using Unphased [18].…”
Section: Methodsmentioning
confidence: 99%
“…-238A allele was observed to be significantly higher in 2009 H1N1 cases than controls and carriage of -238A allele was associated with the development of pneumonia [17]. However, these results are specific to a geographic region and have to be confirmed in different cohort.…”
Section: Discussionmentioning
confidence: 81%
“…So far in only one study conducted by Antonopoulou, et al [17] in Greece, role of -238, -308, -376 SNPs in 109 H1N1 infected patients was studied. -238A allele was observed to be significantly higher in 2009 H1N1 cases than controls and carriage of -238A allele was associated with the development of pneumonia [17].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study found that the lack of Tnf signaling in mice led to increased tissue damage (possibly mediated via MCP-1) during influenza virus infection, even though there was no ultimate difference in clinical outcome [62]. Finally, during the 2009 influenza pandemic, several Tnf associated SNPs identified in human patients were found to be highly correlated with disease severity [63]. Our results show that the replication rates of both X31 and PR8 in the LET-1 cells can be similarly reduced by recombinant Tnf, suggesting that the early induction of Tnf by X31 might contribute to its reduced replication rate in vivo .…”
Section: Discussionmentioning
confidence: 99%